IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 33 TAHUN 1998 TENTANG MODAL PENYERTAAN PADA KOPERASI WANITA “SETIA BHAKTI WANITA” SURABAYA - Arsyad Arsyad (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The title of this study is the Governmental Regulation Implementation of Number 33 Year 1998 About Capital and Also Woman Co-Operation "Devoted of Bhakti Woman" Surabaya, with the problem formula, what will be Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation "Devoted of Bhakti Woman" Surabaya and Factor of whether/what pushing and pursuing Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation "Devoted of Bhakti Woman" Surabaya. As for target expected from this research, is to description and analysis carefully about Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation "Devoted of Bhakti Woman" Surabaya and identify the factor of whether/what pushing and pursuing "Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation "Devoted of Bhakti Woman" Surabaya. The following Usefulness, practically result of this research can give the practical reference to maker and policy executor in formulating and implementation of an policy which is with vision of economic democracy and theoretically this research can give the contribution theoretically for new theory development is which is possible found in researching into of a kind, and also in order to new theory. While for researcher of result of this research is expected can be useful in enriching knowledge and researcher knowledge at one blow can apply it in the world of reality.While its conclusion is its execution is Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation " Devoted of Bhakti Woman" Surabaya walk not yet as according to expectation as formulated. Factor-Factor pushing Governmental Regulation Implementation of Number 33 year 1998 About Capital And Also At Woman Co-Operation "Devoted of Bhakti Woman" Surabaya is factor that is resource factor, factor of disposition and structure factor bureaucracy, while pursuing is communications factor.